2009
DOI: 10.1108/13598540910954502
|View full text |Cite
|
Sign up to set email alerts
|

The best‐practice supplier diversity program at Caterpillar

Abstract: Purpose -The purpose of this paper is to profile the successful implementation of a corporate-wide supplier diversity program utilized by Caterpillar, Inc., one of the Fortune 500 companies. Caterpillar's supplier diversity program can be a blue-print for other companies which would like to accomplish the corporate mission of promoting the free enterprise system by prohibiting restraints of trade, unfair practices, reciprocity, or abuse of economic power. Design/methodology/approach -To comply with stricter go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…From an economic perspective, supplier diversity is the apparatus by which LPOs can obtain valuable product and process insights from EMBs, which can help them obtain a sustainable competitive edge over their competitors that utilize more homogenous, typically White‐owned suppliers that may not necessarily be in tune with what minority consumers desire (Adobor & McMullen, 2007, 2014; Slater, Weigand, & Zwirlein, 2008). The literature also states that EMBs can be more flexible and provide lower minimum‐order quantities in a cost‐effective manner and quicker turnaround times as compared to larger firms, which improves supply chain efficiency while also reducing risk for LPO buyers (Min, 2009). A recent study in the U.K. also found that minority firms have significant innovation to offer potential LPO customers (Nathan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From an economic perspective, supplier diversity is the apparatus by which LPOs can obtain valuable product and process insights from EMBs, which can help them obtain a sustainable competitive edge over their competitors that utilize more homogenous, typically White‐owned suppliers that may not necessarily be in tune with what minority consumers desire (Adobor & McMullen, 2007, 2014; Slater, Weigand, & Zwirlein, 2008). The literature also states that EMBs can be more flexible and provide lower minimum‐order quantities in a cost‐effective manner and quicker turnaround times as compared to larger firms, which improves supply chain efficiency while also reducing risk for LPO buyers (Min, 2009). A recent study in the U.K. also found that minority firms have significant innovation to offer potential LPO customers (Nathan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-sourcing improves up-stream order-volume flexibility that might be needed due to unforeseen demand surges (Ramasesh et al 1991). Supplier diversity could stem from other factors as well (e.g., complying with governmental regulation), as given in Min (2009). At the same time, too many service providers increase administrative costs and prevent the development of a long-term partnership (Dahel 2003).…”
Section: Tactical Considerationsmentioning
confidence: 97%
“…Here they found that such diversity in supplier base is beneficial for buyer. They also found that culture of organization plays major role on supplier diversity and organizations with constructive cultures for diversity had higher minority sourcing and organization with defensive culture have less minority sourcing [58].…”
Section: Supplier Diversitymentioning
confidence: 96%